2010
DOI: 10.1111/j.1467-9566.2010.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Every space is claimed’: smokers’ experiences of tobacco denormalisation

Abstract: Over the past decade, the strategy of 'denormalising' tobacco use has become one of the cornerstones of the global tobacco control movement. Although tobacco denormalisation policies primarily affect people on the lowest rungs of the social ladder, few qualitative studies have explicitly set out to explore how smokers have experienced and responded to these legislative and social changes in attitudes towards tobacco use. Drawing on a qualitative study of interviews with 25 current and ex-smokers living in Vanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 25 publications
5
108
0
1
Order By: Relevance
“…Critics have noted, however, that this 'shaming' approach could increase stigmatisation of lower income smokers and exacerbate existing health inequalities (eg. Bayer, 2008;Bell et al, 2010aBell et al, , 2010b. Therefore we face a situation in the UK where, whilst tobacco use and cigarette smoking continue to fall, a growing market of different and more complex 'delivery systems' and 'vape' products such as e-cigarettes and e-shisha are becoming increasingly popular with some young people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critics have noted, however, that this 'shaming' approach could increase stigmatisation of lower income smokers and exacerbate existing health inequalities (eg. Bayer, 2008;Bell et al, 2010aBell et al, , 2010b. Therefore we face a situation in the UK where, whilst tobacco use and cigarette smoking continue to fall, a growing market of different and more complex 'delivery systems' and 'vape' products such as e-cigarettes and e-shisha are becoming increasingly popular with some young people.…”
Section: Introductionmentioning
confidence: 99%
“…Smoke free legislation has been followed by a public health policy of responsibilisation and stigmatisation of smoking with the intention to 'denormalise' it (Bell et al, 2010a;WHO, 2008), in order to make smoking 'abnormal' and to make individual choices that have resultant personal and social costs "undesirably different" (Goffman, 1963: 15). Critics have noted, however, that this 'shaming' approach could increase stigmatisation of lower income smokers and exacerbate existing health inequalities (eg.…”
Section: Introductionmentioning
confidence: 99%
“…My intention was to challenge tobacco control denormalisation strategies, which had in recent years become implicated with socioeconomic discrepancies in smoking prevalence because such approaches have historically had a greater impact on the better off (Bell, McCullough, Salmon, & Bell, 2010). Evidence showed that mainstream anti-smoking interventions to reduce smoking rates amongst Indigenous peoples had not impacted effectively on smoking (Bond, Brough, Spurling, & Hayman, 2012) but had contributed to the widening of health inequalities (Feldman & Bayer, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In many places, smoking has been made to shift from a standard behaviour to a deviation from the norm. Increasingly, smokers themselves and not only their behaviour are seen as irresponsible, resulting in their stigmatization and social disqualification (Bell et al, 2010). On the one hand, smokers are seen as victims of an 'addiction disease'.…”
Section: Nv and The Smoking-related Health Gapmentioning
confidence: 99%